Experimental evaluation of hybrid cycloconverters - Klumpner, Christian; Xu, Tianning; Clare, Jon C. (2009)
Power converters consisting of naturally commutated thyristors such as cycloconverters and current source inverters were the first used in driving electrical motors with variable speed but now due to their inferior performance compared to forced commutated converters, their use is restricted in the high voltage/high power range where the performance and cost of forced commutated switching devices is not competitive yet. Hybrid cycloconverters proposed recently improve the performance of cycloconverters by adding an auxiliary forced commutated inverter with reduced installed power that enhances the control over the circulating current and improves the quality of the output voltage. This paper evaluates the performance of a few standard and hybrid cycloconverter arrangements using simulation and experimental results.